# Solve for b 9/b=b/4

9b=b4
Multiply the numerator of the first fraction by the denominator of the second fraction. Set this equal to the product of the denominator of the first fraction and the numerator of the second fraction.
9⋅4=b⋅b
Solve the equation for b.
Rewrite the equation as b⋅b=9⋅4.
b⋅b=9⋅4
Multiply b by b.
b2=9⋅4
Multiply 9 by 4.
b2=36
Take the square root of both sides of the equation to eliminate the exponent on the left side.
b=±36
The complete solution is the result of both the positive and negative portions of the solution.
Simplify the right side of the equation.
Rewrite 36 as 62.
b=±62
Pull terms out from under the radical, assuming positive real numbers.
b=±6
b=±6
The complete solution is the result of both the positive and negative portions of the solution.
First, use the positive value of the ± to find the first solution.
b=6
Next, use the negative value of the ± to find the second solution.
b=-6
The complete solution is the result of both the positive and negative portions of the solution.
b=6,-6
b=6,-6
b=6,-6
b=6,-6
Solve for b 9/b=b/4

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top